Role of Law and Justice in Achieving Gender Equality - Chiongson, Rea Abada (Washington, DC: World Bank, 2012)
The authors are grateful to a number of people who helped at various states in the drafting of this paper. In particular, Nicholas Menzies (Justice Reform Specialist, LEGJR) for his continuous support and extensive comments on earlier drafts; Milena Stefanova (Project Officer, LEGJR), Daniel Evans (Consultant, LEGJR) and Elizabeth Morgan (Development Practitioner, PNG-Australia Law and Justice Partnership, Village Courts & Land Mediation Secretariat, PNG Department of Justice & Attorney General) for their invaluable inputs and insights; Barry Walsh (Senior Justice Specialist, LEGJR), Harold Epineuse (Counsel, LEGJR), Richard Nash (Counsel, LEGJR) and Melissa Upreti (Center for Reproductive Rights) for their contributions and comments; Virginia Seitz (Senior Director, Social and Gender Assessment, Millennium Challenge Corporation) and Limpho Masekese Maema (Gender Coordinator, Gender Equality in Economic Rights Programme, Millenium Challenge Account- Lesotho) for their contribution to the drafting of the case study on Lesotho.